2022
DOI: 10.1177/14644207211073445
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional free vibration analysis of functionally graded graphene reinforced composite laminated cylindrical panel

Abstract: In this paper, natural frequency analysis of functionally graded graphene platelet (GPL) reinforced composite cylindrical panel is investigated. Halpin-Tsai equations are employed to obtain the mechanical properties of the structure. The linear three-dimensional elasticity theory based on the Hamilton principle and the numerical finite element method are used for obtaining the governing equations of motion. Four patterns of GPL distributions such as: FG-X, FG-V, FG-O and UD are assumed through the thickness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Hereafter, is used within the numerical investigation. According to the Halpin–Tsai micromechanics model [ 60 ], the elasticity modulus of nanocomposites without internal cavities is defined as with where indices and stand for properties of the metallic matrix and graphene platelets, respectively; is the volumetric content of GPLs; and , and refer to the length, width and thickness of the nano-filler platelets, respectively.…”
Section: Theoretical Problemmentioning
confidence: 99%
“…Hereafter, is used within the numerical investigation. According to the Halpin–Tsai micromechanics model [ 60 ], the elasticity modulus of nanocomposites without internal cavities is defined as with where indices and stand for properties of the metallic matrix and graphene platelets, respectively; is the volumetric content of GPLs; and , and refer to the length, width and thickness of the nano-filler platelets, respectively.…”
Section: Theoretical Problemmentioning
confidence: 99%
“…Masoud Babaei utilized the finite element method to analyze the natural frequencies of functionally graded graphene sheets (GPL) in different distribution modes while considering different material parameters and boundary conditions. The findings revealed that FG-O types exhibited the minimum natural frequencies [13]. Kurzweil investigated the secondary vibration and noise of the surrounding ground induced by high-speed trains and analyzed the law of vibration propagation in different soil layers [14].…”
Section: Introductionmentioning
confidence: 99%
“…The free vibration analysis is an important problem in engineering (see Babaei et al [ 37 ]), and within this context, CUF has been applied to the study of VATs considering PVD as the main variational statement. For this reason, this work aims to extend this framework with the RMVT formulation in order to develop a family of hierarchical plate finite elements.…”
Section: Introductionmentioning
confidence: 99%